CHILD’S EYE HEALTH PREVENTION IN BULGARIA - CURRENT ISSUES - Popova, Katja (Journal of process management and new technologies, 2016)
The care for children`s eyesight protection and keeping is a part of the strategy for the children n` health protection. Child`s excellent vision is extremely important for his or her good physical and psychical development, social adaptation, formation of the entire personality. The purpose of this study is parents` health culture necessary for keeping the children`s sight in a good state. The object of this study is how to provide health education. A thorough analysis has been made on the literature ranging over that problem using the sociological research methods, as following: documentary and inquiry ones; a comparative analysis method. The inquiry was conducted in the month of March - April in 2016. The participants in that research were some accidentally selected parents in the Region of Burgas and parents of pupils attending Mihail Lakatnik Primary Base School in the town of Burgas. The results obtained from the above said inquiry defined negative health behaviors on the part of the predominant group of parents towards the preventive cares for children`s eye health protection. Regardless of the existing Vision 2020 – The Right to Sight Program, a lack of an adequate collaboration has been evidenced among parents, outpatients` assistance specialist, ophthalmologists, health care professionals, teachers. The analysis of the results obtained by the research have demonstrated the necessity to improve parents awareness and raise their responsibility towards children`s eyesight protection and to plan and conduct a series of preventive activities with the purpose of non admission of eye diseases development and traumatic lesions occurrence.